Fans’ Perception on the Influence of Gaming Content Creators and Video Games Fandom on their English Language Acquisition - Zakia, Ashilla; Solusia, Carbiriena (Journal of English Language Teaching, 2025)
The gaming industry has grown significantly in the last several years, becoming one of the entertainment industries with the biggest effects, where gaming content creators and video game fandoms have emerged as huge online communities that primarily use English for communication. This study was conducted to investigate fans' perception on the influence of gaming content creators and video games fandom on their English language acquisition, and which one is seen as more influential. This research used descriptive design with quantitative approach, where data was collected using online questionnaires distributed to 100 Indonesian fans aged 18-24 years old who enjoy watching gaming content creators and are part of video game fandoms. The findings shows that gaming content creators are perceived as slightly more influential than video game fandoms in supporting English language acquisition. Both gaming content creators and video game fandoms provide meaningful opportunities for fans to experience English in natural contexts, which supports language acquisition theory where individuals can acquire language subconsciously when combined with motivation and interest.